SAT0476 Impact of etanercept-methotrexate therapy on patient-reported outcomes in a randomized controlled trial in moderately active rheumatoid arthritis patients. (23rd January 2014) - Bird, P.; Wollenhaup, J.; Lee, S.-H.; Szekanecz, Z.; Neira, O.; Hammond, C.; Vlahos, B.; Szumski, A.; Koenig, A.S.; Kotak, S.
Abstract : Background: Normalization of physical function and health-related quality of life (HR-QoL) is an important treatment goal in patients with rheumatoid arthritis (RA), including those with moderately active disease despite MTX use. Increasing treatment costs, particularly for very effective but expensive biologic agents, have also triggered interest in exploring optimal treatment strategies such as "induction-then-maintenance" regimens. Objectives: To compare patient-reported outcomes (PROs) achieved with continuing etanercept (ETN) 50 mg QW + methotrexate (MTX; E50/M), reducing ETN from 50 mg to 25 mg QW + MTX (E25/M), and replacing ETN with placebo + MTX (P/M) over 52 wks after induction of sustained response during 36 wks of E50/M. Methods: Patients with moderately active RA (DAS28 of >3.2 and ≤5.1) who achieved DAS28 low disease activity (LDA; DAS28 ≤3.2, avg wk 12–36 + at wk 36) during the 36-wk open-label induction phase with E50/M were randomized to double-blind treatment with E50/M (n=202), E25/M (n=202), or P/M (n=200) for 52 wks. PROs included: HAQ; EQ-5D; Medical Outcomes Study Sleep Scale (MOS-SS) Problem I Index; Brief Pain Inventory (BPI); Functional Assessment of Chronic Illness Therapy (FACIT); and Work Productivity Activity Impairment Questionnaire: RA (WPAI:RA). Results: The adjusted mean changes in HAQ, EQ-5D, and WPAI:RA % activity impairment due to RA from wks 36–88 were statistically significantly smaller with E50/M and E25/M vs P/M (table; p<0.0001), indicating less deterioration. Significant differences favoring E50/M and E25/M vs P/M were also observed in the MOS-SS, BPI, FACIT, and WPAI:RA % impairment due to RA while working (p<0.05). The adjusted mean change in % overall work impairment due to RA was significantly smaller with E50/M than with E25/M and P/M at wk 88 (p<0.01). A significantly higher % of patients in the E50/M and E25/M groups reached HAQ Δ ≥0.22 and EQ-5D index Δ ≥0.05 from wks 0 to 88 (p<0.01). Conclusions: In patients with moderate RA disease activity, after induction and maintenance of LDA, etanercept full- and reduced-dose combination regimens were superior to step-down treatment with MTX alone in their effects on PROs. Overall, minimal differences in PROs were observed between the full- and reduced-dose combination treatment groups. Disclosure of Interest: P. Bird: None Declared, J. Wollenhaup Consultant for: Pfizer Inc, S.-H. Lee: None Declared, Z. Szekanecz: None Declared, O. Neira Consultant for: Pfizer Inc, C. Hammond Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Vlahos Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Szumski Employee of: Pfizer Inc, A. S. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Kotak Shareholder of: Pfizer Inc, Employee of: Pfizer Inc